PENGARUH KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA GURU DIMODERASI SUPERVISI (Studi Kasus pada Guru-guru PNS SD di UPT Dinas pendidikan Kecamatan Gunem Kabupaten Rembang) - Dwi Joko Supriyanto, 13.52.02.0076; Srimindarti, Ceacilia (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study was conducted to examine the effect of the variables of teacher competence and Job Satisfaction to the performance of civil service teachers in the district education office UPT Gunem with supervision as a moderating variable.The population in this study was the civil servant teachers in elementary schools-District of Gunem, as many as 113 people. Data were collected using questionnaires and the returned and processed as many as 113 with SPSS 17. Test instruments used are validity and reliability. While model used is the coefficient of determination and test